Multilevel Organisation of Animal Sociality. (September 2020) - Grueter, Cyril C.; Qi, Xiaoguang; Zinner, Dietmar; Bergman, Thore; Li, Ming; Xiang, Zuofu; Zhu, Pingfen; Migliano, Andrea Bamberg; Miller, Alex; Krützen, Michael; Fischer, Julia; Rubenstein, Daniel I.; et al.
Abstract : Multilevel societies (MLSs), stable nuclear social units within a larger collective encompassing multiple nested social levels, occur in several mammalian lineages. Their architectural complexity and size impose specific demands on their members requiring adaptive solutions in multiple domains. The functional significance of MLSs lies in their members being equipped to reap the benefits of multiple group sizes. Here, we propose a unifying terminology and operational definition of MLS. To identify new avenues for integrative research, we synthesise current literature on the selective pressures underlying the evolution of MLSs and their implications for cognition, intersexual conflict, and sexual selection. Mapping the drivers and consequences of MLS provides a reference point for the social evolution of many taxa, including our own species. Highlights: There has been growing recognition of the multilevel nature of many animal social systems but little effort to operationalise it by integrating findings across species. How members of social units in MLSs interact and how dispersal shapes the kinship structure across multiple levels of society is of paramount importance for a holistic understanding of the evolution of sociality. MLSs may offer a flexible solution to a set of socioecological challenges at multiple levels. Whether the structural complexity of MLSs has knock-on consequences for sexual selection, cognition, cultural transmission, and disease dynamics remain important avenues for future research. Understanding the evolution and functional significance of animal MLSs will prove valuable for reconstructing the pillars of human sociality.